Glutamine deficiency in extracellular fluid exerts adverse effects on protein and amino acid metabolism in skeletal muscle of healthy, laparotomized, and septic rats - Holecek, Milan; Sispera, Ludek (Amino acids, 2014)
Characteristic feature of critical illness, such as trauma and sepsis, is muscle wasting associated with activated oxidation of branched-chain amino acids (valine, leucine, isoleucine) and enhanced release of glutamine (GLN) to the blood. GLN consumption in visceral tissues frequently exceeds its release from muscle resulting in GLN deficiency that may exert adverse effects on the course of the disease. In the present study, we investigated the effects of GLN depletion in extracellular fluid on GLN production and protein and amino acid metabolism in skeletal muscle of healthy, laparotomized, and septic rats. Cecal ligation and puncture (CLP) was used as a model of sepsis. After 24 h, soleus muscle (SOL, slow-twitch, red muscle) and extensor digitorum longus (EDL, fast-twitch, white muscle) were isolated and incubated in a medium containing 0.5 mM GLN or without GLN. L-[1-(14)C]leucine was used to estimate protein synthesis and leucine oxidation, 3-methylhistidine release was used to evaluate myofibrillar protein breakdown. CLP increased GLN release from muscle, protein breakdown and leucine oxidation, and decreased protein synthesis. The effects were more pronounced in EDL. Alterations induced by laparotomy were similar to those observed in sepsis, but of a lower extent. GLN deficiency in medium enhanced GLN release and decreased intramuscular GLN concentration, decreased protein synthesis in muscles of intact and laparotomized rats, and enhanced leucine oxidation in SOL of intact and protein breakdown in SOL of laparotomized rats. It is concluded that (1) fast-twitch fibers are more sensitive to septic stimuli than slow-twitch fibers, (2) extracellular GLN deficiency may exert adverse effects on protein and amino acid metabolism in skeletal muscle, and (3) muscles of healthy and laparotomized animals are more sensitive to GLN deficiency than muscles of septic animals.
Keywords: extracelulární tekutina; Muscle Proteins; Male; Rats, Wistar; větvené aminokyseliny; svalové proteiny; sepse; Muscle, Skeletal; Amino Acids, Branched-Chain; laparotomie; mužské pohlaví; potkani Wistar; Sepsis; kosterní svaly; krysa rodu Rattus; Animals; glutamin; Glutamine; zvířata; Rats; Laparotomy; Extracellular Fluid